PENGETAHUAN REMAJA PUTRI TENTANG PERKEMBANGAN ORGAN SEKS SEKUNDER PADA MASA PUBERTAS DI SMP NEGERI 1 LATONG KECAMATAN LUBUK BARUMUN KABUPATEN PADANG LAWAS TAHUN 2018 - ELFINA RIS IMELDA (LP2MTBM MAKARIOZ, 2019)
According to the World Health Organization (WHO) adolescents are residents in the age range of 10-19 years. The results of the Indonesian Youth Demographic and Health Survey (SDKI-R) said 13.3% of young women did not know anything about their physical changes during puberty. Even almost half (47.9%) of young women do not know puberty. The purpose of this study was to determine adolescent knowledge about the development of secondary sex organs during puberty in SMA Negeri 1 Panyabungan.This research method is descriptive, using primary and secondary data conducted by distributing questionnaires to 75 respondents, sampling using Total Sampling. This research was conducted in March. The results were obtained based on the knowledge of the majority of respondents with sufficient knowledge as many as 43 respondents (57.3%), and a minority of respondents who were well knowledgeed were 11 respondents (14.7%). Based on the pattern of life the majority of unhealthy lifestyles were 47 respondents (62.7%), and the minority of healthy lifestyles were 28 respondents (37.3%). Based on information sources, the majority of electronic media were 23 respondents (30.7%), and the minority of print media were 14 respondents (18.7%). From the above data it can be concluded that the knowledge of adolescent girls about the development of secondary sex organs at puberty in SMA Negeri 1 Latong is in the sufficient category. It is expected that young women will further enhance their knowledge, especially about the development of secondary sex organs at puberty.